Container gardening through the year - Hillier, Malcolm (London : Dorling Kindersley, 1995)
Features more than sixty planting projects, with plant quantities, pot dimensions, and growing details for each.
Includes index.
Keywords: Container gardening; Container gardening -- Pictorial works